Taking the measure: a demographic-based study of non-metropolitan Surrey c. 1550-1750 - Jones, SR (2020)
This thesis offers an exploration in a sub-regional context of early modern England’s interconnected demographic and economic systems, revealing some of the patchwork of local experiences which made up the national picture. The study’s findings contribute to a number of discussions. It challenges or develops aspects of some current narratives including on the changing balance between pastoral and arable agriculture, on the 1550s and 1590s mortality crises and on differing patterns of male and female mortality. It also re-emphasises geographical characteristics of migration, though expanding understanding of the origins of London apprentices.